2016
DOI: 10.1097/md.0000000000002533
|View full text |Cite
|
Sign up to set email alerts
|

Natural Transmission Model for Severe Fever With Thrombocytopenia Syndrome Bunyavirus in Villages of Hubei Province, China

Abstract: Severe fever with thrombocytopenia syndrome (SFTS), an emerging high-fatality infectious disease, is caused by a novel bunyavirus. However, a clear natural transmission model has not yet been established.We conducted a cross-sectional study with in-depth investigation of villages to systematically understand the transmission and risk factors among humans, host animals, and vectors. Village residents were interviewed using standardized questionnaires, in which there were confirmed cases of new infections, betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…However, all of the cases in the study were sporadic and not linked epidemiologically, so we did not analyze the variable of “contact with blood or mucous of an SFTS patient”. One study found that there was no statistically significant difference for seroprevalence of SFTSV antibodies between those who had been in close contact with an SFTS patient and those who had not [27], suggesting that person-to-person transmission is not the main risk factor for infection, and this mode of transmission is probably limited.…”
Section: Discussionmentioning
confidence: 99%
“…However, all of the cases in the study were sporadic and not linked epidemiologically, so we did not analyze the variable of “contact with blood or mucous of an SFTS patient”. One study found that there was no statistically significant difference for seroprevalence of SFTSV antibodies between those who had been in close contact with an SFTS patient and those who had not [27], suggesting that person-to-person transmission is not the main risk factor for infection, and this mode of transmission is probably limited.…”
Section: Discussionmentioning
confidence: 99%
“…Although human-to-human transmission has been reported in China and South Korea,79 SFTS is transmitted mainly by ticks; Ixodidae ticks, in particular, are implicated as vectors of SFTSV 1,10,11. A previous study in South Korea reported that the minimum infection rate of SFTSV in Haemaphysalis longicornis ticks, major vectors of SFTSV, was 0.46% 12.…”
mentioning
confidence: 99%
“…Severe fever with thrombocytopenia syndrome (SFTS) is an emerging viral hemorrhagic fever that was first identified in China (1), with cases since reported in Japan, South Korea, Vietnam and Taiwan (2,3). SFTS virus (SFTSV) has been identified as a causative virus of SFTS belonging to the genus Banyangvirus, family Phenuiviridae, order Bunyavirales.…”
Section: Introductionmentioning
confidence: 99%
“…SFTS has been considered to be mainly transmitted by tick bites. Ticks infest a variety of animals, and viral RNA and antibodies against SFTSV have been detected in wild animals, domestic animals and companion animals, such as dogs and cats [1][2][3][4][5]. Since these animals show no clinical symptoms, they have been considered subclinically infected with SFTSV.…”
Section: Introductionmentioning
confidence: 99%